Effects of dynamic 3D-volume of side chains in conjugated polymers on nano-scale morphology and solar cell properties - Park, Sungmin; Seo, Dongkyun; Kwak, Kyungwon; Chung, Dae Sung; Cheon, Cheol Hong; Kim, BongSoo; Son, Hae Jung (ELSEVIER SCI LTD, 2015)
We have synthesized a series of benzo[1,2-b:4,5-b']-dithiophene (BDT)-co-thieno[3,4-b]thiophene (TT) based polymers with various alkyl side chains and bridging-atom on their TT units and studied the effects of the variation in the effective van der Waals volumes (eVol) of the side chains on the photovoltaic properties of the associated bulk heterojunction (BHJ) solar cells. eVol was found to be correlated with the degree of phase separation in the BHJ film, which affects the area of the polymer-PC71BM interface and the charge mobility. The polymer has a 2-ethylhexyl group that results in a relatively optimal BHJ film morphology, with sufficient polymer-PC71BM interfacial area for efficient charge generation and minimal charge mobility loss upon BHJ film formation. As a result, the solar cell device (2-ethylhexyl polymer) exhibits the highest power conversion efficiency of 8.25% because its short-circuit current density value (16.24 mA/cm(2)) and fill factor (0.674) are the highest of the synthesized polymers. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: POWER CONVERSION EFFICIENCY; HIGH-PERFORMANCE; NANOMORPHOLOGY; AGGREGATION; DESIGN